(3GdebOeI aj Yde GdMSGHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s ((3MSf Hf eMeO Hf jYbhH GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg HdG YOO hGdBNQ HdG CeO hGdUdGI hGdSdGe Ydi fHjg GdChai GdfGWb HGdUhGH s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeOq s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdfSNI HgG MhGTs
(3GdfSNI efbhdI Yf fSNI HNW GdeDda ceG ai BNQgGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdQjGVjGJs